A refined five-unknown higher-order model including transverse normal hygrothermal deformation. (15th September 2016) - Wu, Zhen; Xu, Qi; Lu, Shaowei; Ren, Xiaohui
Highlights: A five-unknown model is extended to include three-dimensional hygrothermoelastic deformations. Transverse normal strain is considered without increase of additional displacement parameters. The proposed model is suitable for analysis of multilayered composites under hygrothermal loads. Abstract: Hygrothermoelastic stress has strong impact on composite structures due to their intrinsic heterogeneity, so five-unknown higher-order models have been usually employed for hygrothermal bending analysis of composite plates. If these models are used to analyze hygrothermal expansion problem, inaccurate conclusion will be drawn as transverse normal strain is neglected. Thus, a refined five unknown higher-order model including transverse normal hygrothermal deformation will be developed. In order to include the transverse normal deformation, the hygrothermal deformation through the thickness due to the thermal and moisture loads is introduced in the transverse displacement field. Applying the bounding surface free traction condition, effects of transverse normal hygrothermal deformation can be incorporated in the in-plane displacement field which can actively influence the accuracy of in-plane stresses. By analyzing hygro-thermo-mechanical behaviors of multilayered composite plates, effects of different temperature, number of layers and transverse normal strain on the displacements and stresses of composite plates have all been studied. Through the numerical examples of hygrothermal analysis, the accuracy and efficiency of the proposed model are demonstrated.